2020
DOI: 10.3390/su12208390
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Exhibitor Satisfaction and Loyalty: A Meta-Analysis on the Chinese Exhibition Market

Abstract: With the exhibition sector becoming increasingly important for the hospitality and tourism industry, it is critical to understand what drives the success of an exhibition. Through a comprehensive literature review, we first identified two broad categories of factors, namely exhibition attributes and exhibitor perceptions, that influence exhibitor satisfaction and loyalty. Next, a meta-analysis was conducted based on 26 empirical papers studying the Chinese exhibition market to quantitatively evaluate these rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In the context of an exhibition, the role of satisfaction greatly attracts scholars' attention as level of satisfaction helps the destination to organize the exhibition, thus increase the exposure of the destination's brand. Many scholars have identified the antecedents of attendants' satisfaction at an exhibition, such as service quality (Chen & Mo, 2012), knowledge transfer (Wong & Lai, 2018), exhibitor perception and attributes (Liu et al, 2020).…”
Section: Overall Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of an exhibition, the role of satisfaction greatly attracts scholars' attention as level of satisfaction helps the destination to organize the exhibition, thus increase the exposure of the destination's brand. Many scholars have identified the antecedents of attendants' satisfaction at an exhibition, such as service quality (Chen & Mo, 2012), knowledge transfer (Wong & Lai, 2018), exhibitor perception and attributes (Liu et al, 2020).…”
Section: Overall Satisfactionmentioning
confidence: 99%
“…Sung and Lee (2015) also identified that attendant's satisfaction depends on the conference's overall service performance. Visitors' satisfaction can be testified according to the exhibition attributes (Liu et al, 2020). Therefore, if attendants gain a good experience from the exhibition, the three types exhibition attributes may influence their overall satisfaction of the exhibition.…”
Section: Overall Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a product/brand-centered process when the loyalty state of mind is constructed around the very characteristics and attributes of the product or service itself, using websites just as a means to reach the products and transfer information to complete the buying process. The second one is related to the website being the intention to repurchase on the same website and to recommend it through different online or mobile channels even if it is not the same product [23][24][25]. In this case, we speak about loyalty toward the website itself.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…The causal relationship between the variable accessibility and trust is based on the same need for the new type of consumer-fast solutions, at hand, to be able to consume the necessary products in crisis conditions [23]. Thus, websites that invest enough in optimizing accessibility give the consumer the feeling that he is dealing with a reliable business, directly interested in his needs-the ease of accessing and placing orders and the reliability of the process.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%